(untitled) (The Agriculturists, 2019)
The study was conducted at the Stress Research Site of the Department of Agronomy of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur, Bangladesh during the period from April to July 2017 to evaluate the effect of rescue nitrogen fertilizer for improving the performance of waterlogging tolerance in mungbean genotype VC-6173A. Both waterlogged and non-waterlogged mungbean plants were received varying doses of rescue nitrogen from urea fertilizer. The rescue nitrogen (N) treatments were: N0-no rescue N; N30 - 20 and 10 kg ha-1 rescue N applied at 0-day and 15-day after removal of waterlogging (ARW); N40 - 30 and 10 kg ha-1 rescue N applied at 0-day and 15-day ARW and N50 - 40 and 10 kg ha-1 rescue N applied at 0-day and 15-day ARW. The study was laid out in a randomized complete block design with four replications. Different levels of rescue N improved plant height, leaf chlorophyll index, phonological period, plant growth, pod formation and seed yield of mungbean. N-treated plants showed higher relative SPAD chlorophyll values and the increment was higher for higher N-dose. Waterlogging reduced 40% root dry matter and 34% both shoot and total dry matter relative to non-waterlogged plants. Rescue N significantly increased both the root and shoot dry matter. The waterlogged plants without rescue N showed 29% reduction in the number of pods per plant and the reduction showed 13% for rescue N40 in waterlogged plants. The seed yield reduction was 25% in waterlogged plants without rescue N but with rescue N, seed yield remarkably increased particularly in N40-treated plants. Therefore, the study suggests that rescue N fertilizer application may be a viable practice in improving waterlogging tolerance and increasing yield of mungbean. The Agriculturists 2019; 17(1-2) 01-13